2018
DOI: 10.3389/fimmu.2017.01773
|View full text |Cite
|
Sign up to set email alerts
|

The CXCR4–STAT3–IL-10 Pathway Controls the Immunoregulatory Function of Chronic Lymphocytic Leukemia and Is Modulated by Lenalidomide

Abstract: Chronic lymphocytic leukemia (CLL) cells possess regulatory functions comparable to those of normal B10 cells, a regulatory B cell subset that suppresses effector T-cell function through STAT3-mediated IL-10 production. However, the mechanisms governing IL-10 production by CLL cells are not fully understood. Here, we show that the CXC chemokine ligand 12 (CXCL12)–CXCR4–STAT3 axis regulates IL-10 production by CLL cells and their ability to suppress T-cell effector function through an IL-10 mediated mechanism. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…In acute myeloid leukemia cells, murine plasmacytomas, and hybridomas, the autocrine secretion of interleukin-6 caused phosphorylation of STAT3, Tyr705 and Ser727 (9,26), including STAT3-mediated constitutive expression of SOCS-3 in cutaneous T-cell lymphoma (27). In addition, STAT3 also plays a pivotal role in the progression of hematological malignancies, including CLL (28)(29)(30). In the present study, our results revealed that pSTAT3 expression was elevated in PBMCs from CLL patients.…”
Section: Discussionmentioning
confidence: 99%
“…In acute myeloid leukemia cells, murine plasmacytomas, and hybridomas, the autocrine secretion of interleukin-6 caused phosphorylation of STAT3, Tyr705 and Ser727 (9,26), including STAT3-mediated constitutive expression of SOCS-3 in cutaneous T-cell lymphoma (27). In addition, STAT3 also plays a pivotal role in the progression of hematological malignancies, including CLL (28)(29)(30). In the present study, our results revealed that pSTAT3 expression was elevated in PBMCs from CLL patients.…”
Section: Discussionmentioning
confidence: 99%
“…In hematological malignancies, as well as in solid tumors, the overexpression of CXCR4 is responsible for metastasis in organs expressing high CXCL12 levels (e.g., lymph nodes and BM), in addition to disease progression, increased tumor cell survival, and chemoresistance [98]. In chronic lymphocytic leukemia (CLL), the CXCL12/CXCR4 axis induces immune suppression via Signal Transducer and Activator of Transcription 3 (STAT3) phosphorylation in B and T-CLL cells [99]. Recently, p66Shc was identified as a negative regulator of CXCR4 endosome recycling in CLL [100].…”
Section: Cxcl12/cxcr4 Axis In Hematological Tumors: a Crucial Hub Formentioning
confidence: 99%
“…Further, STAT3 regulates cytokine production in CLL cells. STAT3 was found to regulate the secretion of IL-9 and IL-10 in CLL cells [18,30]. STAT3-mediated translational upregulation of miR-155 and miR-21 promoted IL-9 secretion [18].…”
Section: Effect Of Stat3 On Cll Cell Metabolismmentioning
confidence: 99%
“…STAT3-mediated translational upregulation of miR-155 and miR-21 promoted IL-9 secretion [18]. Concerning IL-10, the CXCL12-CXCR4-STAT3 axis regulates IL-10 production in CLL cells and their ability to suppress T-cell effector function [30].…”
Section: Effect Of Stat3 On Cll Cell Metabolismmentioning
confidence: 99%